2011
DOI: 10.1007/s11104-011-0823-x
|View full text |Cite
|
Sign up to set email alerts
|

Variation for nodulation and plant yield of common bean genotypes and environmental effects on the genotype expression

Abstract: Common bean symbiotic nitrogen fixation provides an ecological and economical alternative to increase bean production but it depends on soil fertility and climate conditions. The objectives of this work were to characterize common bean genotypes for their ability to establish symbiosis under controlled conditions and to study the effect of the environment on the expression of those genotypes. The experiment under controlled conditions was conducted in a greenhouse with 158 genotypes that represented the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 65 publications
5
20
0
Order By: Relevance
“…Due to genetic makeup difference among common bean genotypes, it may record high production though induced low nodulation (Pereira et al 1984). Conversely, Rodiño et al (2011) found that genotypes with a big nodule phenotype showed a good plant response and more beneficial for plant growth and seed yield. In contrast to the current study, Farid and Navabi (2015) found the common bean genotypes × environment interaction for grain yield production.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to genetic makeup difference among common bean genotypes, it may record high production though induced low nodulation (Pereira et al 1984). Conversely, Rodiño et al (2011) found that genotypes with a big nodule phenotype showed a good plant response and more beneficial for plant growth and seed yield. In contrast to the current study, Farid and Navabi (2015) found the common bean genotypes × environment interaction for grain yield production.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests the presence of appropriate indigenous rhizobia, which could be different in infectiveness and effectiveness in different soils. Rodiño et al (2011) determined common bean variety and variety × environment interaction effect on nodulation. A similar finding was reported in common bean in Canadian Prairie by Nleya et al (2009) who found that common bean genotypes differed in nodulation formation.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of rhizobia symbiotic system, it is possible that migration of the species had not been parallel, so additional efforts are under way to achieve efficient symbiotic genotypes of common bean and rhizobia (Rodiño et al, 2011). As a result of plantrhizobia co-evolution, a spectrum of compatible rhizobia has developed each specific for one or more given legume species.…”
Section: Evolution Of the Crop Beyond Its Areas Of Origin And Domestimentioning
confidence: 99%
“…The fact that the common bean has evolved wordlwide outside its areas of origin has implications for the development of new varieties in its areas of adaptive radiation, such as Europe. For the rhizobia symbiotic system, it is possible that migration of species had not been parallel, so additional efforts are under way to achieve efficient symbiotic genotypes of common bean and rhizobia (Rodiño et al, 2010;Rodiño et al, 2011).…”
Section: Downloaded By [Mcmaster University] At 11:34 05 December 2014mentioning
confidence: 99%
“…The efficiency of the symbiotic pathway for accumulating N and for the plant to store it as proteins of good nutritional value, is the ultimate goal of most breeding programs. These traits are very integrative and quantitative, and are based on several plant functions and numerous plant genes, together with environmental factors (Santalla et al, 2001b;Rodiño et al, 2011).…”
Section: Optimizing Symbiotic Activities Andmentioning
confidence: 99%